2020
DOI: 10.1016/j.ijantimicag.2020.106017
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio and clinical outcome in COVID-19: a report from the Italian front line

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
94
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 4 publications
15
94
0
1
Order By: Relevance
“…Neutrophil to Lymphocyte ratio (NLR) has been explored as a prognostic marker for COVID-19, with high level of NLR associated with severity of the disease 43,44 or with higher mortality rates 45,46 . More specific subsets of the Lymphocytes, especially the CD4 + and CD8 + T-cell counts are found to be depleted in severe COVID-19 patients 17,47 .…”
Section: Relationship With Immune Cellsmentioning
confidence: 99%
“…Neutrophil to Lymphocyte ratio (NLR) has been explored as a prognostic marker for COVID-19, with high level of NLR associated with severity of the disease 43,44 or with higher mortality rates 45,46 . More specific subsets of the Lymphocytes, especially the CD4 + and CD8 + T-cell counts are found to be depleted in severe COVID-19 patients 17,47 .…”
Section: Relationship With Immune Cellsmentioning
confidence: 99%
“…Various parameters have been proposed to predict prognosis and outcomes among patients with COVID, including the neutrophil to lymphocyte ratio (NLR) (27)(28)(29)(30). A metanalysis of six studies involving 1,141 patients has demonstrated that an elevated NLR is associated with severe disease manifestation (28).…”
Section: Introductionmentioning
confidence: 99%
“…Another Chinese study performed in Hubei Provincial Hospital of Integrated Chinese and Western Medicine included 32 moderate and 31 severe cases and found an optimal cut-off of NLR >4.7 is an independent risk factor for severe COVID-19 [ 7 ]. Afterward, a European study conducted in Italy showed that severe patients are also older and had higher NLR compared with non-severe patients, suggesting that NLR may be a useful marker to early screening of COVID-19 patients [ 8 ]. Surprisingly, the risk of in-hospital mortality is 8% higher for each unit increase of NLR (OR: 1.08, 95%CI: 1.01–1.14), and patients from tertile 3 (NLR 4.85–88.09) have a 15-fold higher risk of death than patients from tertile 1 (NLR 0.54–2.21) [ 9 ].…”
mentioning
confidence: 99%